Application of Flap in Repairing Defect of Orbital Tumor - Ma, Ying-Hui; Liu, Gang; Yang, Jie (Nepalese Journal of Cancer, 2019)
Introduction: Orbital tumors can extensively damage the upper and lower eyelid, peri-orbital skin, periorbital peri-bulbar tissue and eyeball. The complete removal of the tumor and the tissue destroyed by the tumor often leaves a large tissue defect area. Therefore, the application of flap in repairing defect after exenteration of orbital tumor is of paramount importance. The objective of this study is to investigate the clinical value of skin fl ap in repairing defect after exenteration of orbital tumor. Methods: From January 2008 to December 2017, there were 101 patients with orbital tumors, including 47 malignant and 54 benign tumors. All patients underwent excision of tumor while skin flap was used to repair tissue defects of different degrees. Postoperative observation showed the survival and functional recovery of tissue flap. Results: The skin flaps of the patients were completely alive after operation, the defect was completely closed, and the flaps were viable as of color of the flaps. Quality of life score significantly improved after flap surgery. Conclusion: The flap is used to repair the skin defect after orbital tumor surgery, which is helpful to improve the quality of life of patients with orbital tumor.